Editorial for the Special Issue “Novel Echocardiographic Techniques for the Assessment of Cardiovascular Disease” - Konstantinos Katogiannis (Medicina, 2025)
The global burden of cardiovascular disease (CVD) continues to pose a significant challenge to healthcare systems worldwide [...]